2017
DOI: 10.1111/mmi.13765
|View full text |Cite
|
Sign up to set email alerts
|

Functional redundancy of division specific penicillin‐binding proteins in Bacillus subtilis

Abstract: SummaryBacterial cell division involves the dynamic assembly of a diverse set of proteins that coordinate the invagination of the cell membrane and synthesis of cell wall material to create the new cell poles of the separated daughter cells. Penicillin‐binding protein PBP 2B is a key cell division protein in Bacillus subtilis proposed to have a specific catalytic role in septal wall synthesis. Unexpectedly, we find that a catalytically inactive mutant of PBP 2B supports cell division, but in this background th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 56 publications
4
56
0
Order By: Relevance
“…This suggests that PBP1 has a second role, as previously proposed 19 . Compatible results have been obtained in B. subtilis, where introduction of a point mutation in the TP active site of the essential protein PBP2B, did not lead to loss of cell viability 20 .…”
Section: Roda-pbp3 and Ftsw-pbp1 Form Cognate Pairs In S Aureusmentioning
confidence: 87%
“…This suggests that PBP1 has a second role, as previously proposed 19 . Compatible results have been obtained in B. subtilis, where introduction of a point mutation in the TP active site of the essential protein PBP2B, did not lead to loss of cell viability 20 .…”
Section: Roda-pbp3 and Ftsw-pbp1 Form Cognate Pairs In S Aureusmentioning
confidence: 87%
“…(9,40,41) PBP2b, encoded by pbpB, is the only PBP that is essential for growth in B. subtilis, which is attributed to its major role in septum formation. (10,41,42) More recently, it was revealed that the transpeptidation activity of PBP2b is dispensable and cells containing deactivated PBP2b maintain normal growth and morphology. (10, 11) Thus, the development of chemical tools that can selectively target the activity of these transpeptidases can complement the genetic studies and deepen our knowledge about these PBPs, which will be the subject of future work.…”
Section: Selectivity Profile Of β-Lactams For B Subtilis Pbpsmentioning
confidence: 99%
“…(7,8) Functional redundancy within the PBPs has compounded the difficulties in establishing the role of individual PBPs in peptidoglycan biosynthesis. (9)(10)(11) Single PBPs have been studied by conjugation to fluorescently labeled protein tags. (10,12) However, these data alone are insufficient to fully characterize their roles as protein localization does not provide information about the activity state of the PBPs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations